Signaling pathways mediating the induction of preharvest fruit drop in litchi - Wang, Jun; Ma, Wuqiang; Wang, Fei; He, Zidi; Ye, Xiangyang; Deng, Jiahui; Zhao, Minglei; Li, Jianguo (Frontiers in Plant Science, 2024)
Certain litchi varieties, such as "Nuomici", are highly susceptible to preharvest fruit drop, which leads to significant losses in fruit yield and economic value. However, the precise molecular mechanisms underlying this issue are not yet fully understood. In this study, we aimed to elucidate the signaling pathways that facilitate preharvest fruit drop in litchi, using "Nuomici" and "Huaizhi" cultivars as examples, which demonstrate high and low preharvest fruit drop rates, respectively. Our findings revealed that "Nuomici" experienced a substantial preharvest fruit drop, with a cumulative rate of 41.68%, significantly higher than the 1.44% observed in "Huaizhi". Cellulase activity assays showed a significant increase in cellulase activity in the abscission zone of "Nuomici", which coincided with the occurrence of preharvest fruit drop, in contrast to the relatively low levels in "Huaizhi". Phytohormone assays indicated lower indole-3-acetic acid content in the pericarp, aril, and seeds of "Nuomici" during the preharvest stage compared to "Huaizhi", coupled with higher abscisic acid levels in the seeds of "Nuomici". Furthermore, transcriptomic analysis identified 180, 282, 655, and 241 differentially expressed genes (DEGs) in the pericarp, aril, seed, and abscission zone, respectively, between the two cultivars during preharvest fruit drop. These DEGs are intricately involved in the generation and transmission of abscission signals from fruit tissues, encompassing PIN, PIN-LIKES, LAX, and SAUR genes related to polar auxin transport, ethylene diffusion, as well as perceiving these signals and activating the abscission process within the abscission zone. This includes ACO and ILR genes involved in hormone biosynthesis and signal transduction, regulation by WRKY, NAC, and bHLH transcription factors, AAO genes involved in response to reactive oxygen species, and EXP, EG, and PG genes involved in cell wall degradation in the abscission zone. Based on these comprehensive findings, we propose a model for preharvest fruit drop triggered by a series of molecular events in litchi, providing valuable insights into the complex mechanisms governing this phenomenon.